DEVELOPMENT OF E-BOOKLET HISTORY LEARNING MEDIA ON MATERIAL ON THE ORIGINS OF INDONESIAN ANCESTORS AND THE SPICE PATH IN THE PRIVATE PERIOD OF CLASS X OF SENIOR HIGH SCHOOL - Maryati Maryati; Umi Hartati; Johan Setiawan (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to develop an E-Booklet-based learning media on the topic of the origins of the ancestors of the Indonesian nation and the spice routes during the prehistoric era for Class X students at SMA Muhammadiyah 1 Metro. The research method used is Research and Development (R&D) with Sugiyono's Level 1 development model, which includes the stages of needs analysis, product design, expert validation, and revision. Data collection was conducted through interviews, questionnaires, and observations with teachers and students. The research results show that the (1) learning media at SMA Muhammadiyah 1 Metro is still lacking in variety and innovation, causing students to struggle in understanding history material. (2) The developed E-Booklet is designed to provide a more engaging summary of the material, equipped with relevant images and videos. Expert validation in both material and media shows that this E-Booklet is suitable for use in learning.The implication of this research is (3)that the use of E-Booklet media can increase student interest and understanding of history material, particularly on the topic of the origins of the ancestors of the Indonesian nation and the spice routes, as well as encourage the application of technology in history learning at schools.